(untitled) (Fiep Bulletin - online, 2014)
This essay has as central theme the theory and principles that usually command the researches - circumstantial evidence of indicium’s paradigm. Sigmund Freud, initiate in studies of the human comport mental and conduct, Sherlock Holmes, heroic and romantic invention’s Conan Doyle writer, plus at both, a art critic Morelli, Giovanni Morelli, pseudonymous Ivan Lermoieff, characters Carlo Ginzburg of "Mitti emblemi spie: morfologia e storia" (Original Title). To going away this names, Ginzburg elaborate discuss about the paradigm of the "to know circumstantial evidence", one knowledge method, whose force are particularity revel observation, plus at that in the deduction. In "Mitti emblemi spie", the writer to applicator the methods for themes apparent despairs: the history of the popular culture, the theory and the art history, the history of the master art at psychoanalysis, fructiferous a judicial inquire detective investigation that, to bear at light negligence details, revels surprises perspective and to have a right to text epigraph: "God is in particular".